A performance-based decision-making tool for supply chain reengineering - (:unkn) unknown (Inderscience Publishers, 2011)
The purpose of this paper is to present a decomposition-based decision-making tool incorporating supply chain balanced scorecard performance measures for supply chain reengineering. Following a literature review on supply chain performance measures and reengineering models, various dimensions and approaches to supply chain reengineering are explored. Based on the insights gained, using the axiomatic design technique, a performance-based supply chain reengineering model is developed. In line with literature, the study conveys that there is still a large room for improvement for developing balanced supply chain measures that address different parts of the supply chain. This paper focuses on supply chain reengineering models where no conclusive work exists and is expected to fill a gap in the area and be instrumental to both researchers and practitioners by providing a direction for coherent decision-making on supply chain reengineering studies. Copyright © 2011 Inderscience Enterprises Ltd.
Keywords: Axiomatic design; Decomposition; Performance measurement; Reengineering; Supply chain management